The Influence of Brand Image on Interest to Buy and Stove Product Purchase Decision Rinnai at Home Smart - Nurul Amalia; Cahyo Pramono; Rindi Andika (Rowter Journal, 2022)
This research was conducted to explain the partial or simultaneous influence of brand image variables consisting of company image, user image and product image on buying interest and purchasing decisions. The total population used was 96 respondents consisting of consumers who were taken using a questionnaire which was used as a data collection method in this study. This study uses path analysis (path analysis). The results of the analysis show that there is a significant influence partially or simultaneously between the brand image variables consisting of company image, user image and product image on buying interest and purchasing decisions.